2003
DOI: 10.1161/01.hyp.0000083511.91817.b1
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-α and Receptor-γ Activators Prevent Cardiac Fibrosis in Mineralocorticoid-Dependent Hypertension

Abstract: Abstract-Peroxisome proliferator-activated receptor (PPAR) activation may prevent cardiac hypertrophy and inhibit production of endothelin-1 (ET-1), a hypertrophic agent. The aim of this in vivo study was to investigate the effects of PPAR activators on cardiac remodeling in DOCA-salt rats, a model overexpressing ET-1. Unilaterally nephrectomized 16-week-old Sprague-Dawley rats (Uni-Nx) were randomly divided into 4 groups: control rats, DOCA-salt, DOCA-saltϩrosiglitazone (PPAR-␥ activator, 5 mg/kg per day), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 42 publications
8
99
0
2
Order By: Relevance
“…This promotes normalization of collagen turnover 10,18 and contributes, in part, to the improved LV structure and maintenance of normal LV function seen with fenofibrate. These findings complement previous reports that fenofibrate inhibits myocardial fibrosis and inflammation by inhibiting p38, 26,43 nuclear factor-B signaling pathways, 44 suppressing prohypertrophic and redox-regulated transcription factors, 28,31 cardiac endothelin-1 production, 26,45,46 and inhibiting MMP-9. 16 Additionally, both PPAR-␣ and PPAR-␥ agonists inhibit TGF-␤ signaling by interacting with Smad transcription factors [47][48][49] and although speculative, may constitute a mechanism for PPAR-␣-mediated inhibition of TGF-␤-regulated gene expression in aldosterone-induced fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…This promotes normalization of collagen turnover 10,18 and contributes, in part, to the improved LV structure and maintenance of normal LV function seen with fenofibrate. These findings complement previous reports that fenofibrate inhibits myocardial fibrosis and inflammation by inhibiting p38, 26,43 nuclear factor-B signaling pathways, 44 suppressing prohypertrophic and redox-regulated transcription factors, 28,31 cardiac endothelin-1 production, 26,45,46 and inhibiting MMP-9. 16 Additionally, both PPAR-␣ and PPAR-␥ agonists inhibit TGF-␤ signaling by interacting with Smad transcription factors [47][48][49] and although speculative, may constitute a mechanism for PPAR-␣-mediated inhibition of TGF-␤-regulated gene expression in aldosterone-induced fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…PPAR␣ expression is increased in blood vessels of spontaneously hypertensive rats (22), and fenofibrate lowers blood pressure in these rats (11,23). Fenofibrate also prevents cardiac fibrosis in mineralocorticoid-dependent hypertensive rats (24). C-reactive protein upregulates AT 1 R in vascular smooth muscle cells, and these effects are attenuated by losartan (25).…”
Section: Effects Of Therapies On Adiponectin and Insulin Resistancementioning
confidence: 99%
“…Extracts of Shiliuhua had been previously reported to activate PPAR and induce PPAR expression. We found that ethanolic extract of Shiliuhua significantly activated both PPAR and PPAR, which might account for its anti-fibrotic activity since agonists of PPAR (Toyama et al, 2004;Iglarz et al, 2003) and PPAR (Milam et al, 2008;Kawai et al, 2008;Iglarz et al, 2003) were previously reported to suppress fibrosis of liver, lung, heart and kidney. Contrary to our hypothesis, we found that the antifibrotic activities of Shiliuhua extract can only be partially blocked by GW6471, a PPAR antagonist, at a dose 42-fold of its reported IC 50 .…”
Section: Shiliuhua and Pparmentioning
confidence: 61%